HADIS DAN PERANNYA DALAM TAFSIR KONTEKSTUAL PERSPEKTIF ABDULLAH SAEED - Suryadilaga, Muhammad Alfatih (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
The article highlights Abdullah Saeedâs thought in the light of hadith to promote contextual interpretation of the Qurâan. He emphasizes the significance of Hadith to reach best understanding of Qurâan by putting Hadith as historical reflection of Qurâanic worldview. He argues for five principles that should be implemented in examining Hadith as the source of contextual Qurâanic interpretation. He also highlights the difference of sunnah and Hadith, in which Hadith is perceived as collective cognition not as individual individual perception. Further, he also suggests that understanding Hadith could also be actualized by collective reasoning and human nature (fiá¹rah) and it should be totally relevant to the Qurâan. Those are the prerequisite of Hadith as the existing source for Qurâanic interpretation. If Hadith doesnât meet the conditions, although it sounds in terms of chain transmission, the Hadith should be reviewed and even rejected.